An Analytical Study of Buddhavaṃsa Scripture in Palm Leaf Scripture of Watsungmen, Sungmen District, Phrae Province - Kittivanno, PhrakrusangharakBoonserm; Kanka, Sukhum; Ketuveerapong, Poonsub; Suwannapa, Chaweewan; Sricomepa, Raweerose; Supamethesakul, Sermsil; PhrakruVibulsarapan (Journal of International Buddhist Studies, 2018)
The objectives of this study were 1) to translate the Palm Leaf Scripture on Buddhavaṃsa of Wat Sungmen, Sungmen District, Phrae Province, 2) to analyze the content of the Palm Leaf Scripture on Buddhavaṃsa of Wat Sungmen, Sungmen District, Phrae Province and 3) to analysis the writing form the Palm Leaf Scripture on Buddhavaṃsa of Wat Sungmen, Sungmen District, Phrae Province. It was a documentary research by using collecting the Palm Leaf Scripture on Buddhavaṃsa of Wat Sungmen, Sungmen District, Phrae Province and then translated and content analysis. The results showed that; 1) There were 25 volumes of the Palm Leaf Scripture on Buddhavaṃsa of Wat Sungmen, Sungmen District, Phrae Province that was translated from the Lanna language to Thai version from the volume 1-25. There were 283 pages. 2) The content of the Palm Leaf Scripture on Buddhavaṃsa of Wat Sungmen, Sungmen District, Phrae Province could be divided in to 3 characteristics namely; 1) The content structures about the Buddhist Lent and the history of the Load Buddha 2) The content structures about the history of the Sumet Bikkhu and 3) The content structures about the history of 25 the Loard Buddhas. 3. The writing form the Palm Leaf Scripture on Buddhavaṃsa of Wat Sungmen, Sungmen District, Phrae Province was a prose that had the first introduction to the Loard Buddha. The stories explain was conversation or answer, question between the Loard Buddha with Ananda Bikkhu. In term of the compound expand explain the writer took the story appeared on the different scripture to present for further understanding. In part of conclusion had Pali verse or spell cited before ending by presenting the Dhamma to practice or avoids practicing.